Field Experimental Study on the Broken Rock Zone of Surrounding Rock and the Rock Borehole Shear Tests of the Large Deformation Tunnel - Guansheng Han; Bo Meng; Hongwen Jing; Jiangyu Wu (Advances in Materials Science and Engineering)
A large deformation tunnel in LIXIANG railway, named Zhongyi tunnel is located in Southwest of China, was taken for the engineering background. The field experiments of the broken rock zone and the borehole shear test were conducted. The results show that the range of the broken rock zone of the test sections is 4.20∼4.45 meters. The cohesive force and the internal friction angle of the test sections are 221.4∼224 kPa and 14.25∼15.14°, respectively. The test results are in good agreement with the status of the surrounding rock. The surrounding rock is mainly composed of shale, which is badly broken, and the integrity and the stability are poor. In this study, the reasons for the deformation and instability of the tunnel are analyzed combined with the in situ tests and the site condition, and the suggestions for the tunnel support are put forward. This study is of great significance to ensure the safety of the constructors and can improve the service years of the tunnel. In addition, it can provide reference for the same type of the tunnel construction.